Topologies for inverter like operation of power cycling tests. (September 2016) - Herold, C.; Seidel, P.; Lutz, J.; Bayerer, R.
Highlights: Inverter-like operated IGBTs showed expected lifetime for short on-period of 60 ms. New test bench concept for heating by forward and switching losses at low DC link voltage Dimensioning and required circuitry explained